1996
DOI: 10.1111/j.1365-2044.1996.tb13635.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect on the heart of hypoxaemia in patients with severe coronary artery disease

Abstract: SummaryThe aim of the study was to examine the effect of Key wordsHypoxia. Heart; ischaemia, coronary occlusion.Smokers and overweight patients may have ischaemic heart disease and following upper abdominal or thoracic surgery such patients usually have prolonged and profound postoperative hypoxaemia [ 11. The worst hypoxaemia is often on the second and third nights but can be maximal on the fourth. In these circumstances, profound oxygen desaturation (Sao? < 80%) can occur without being noticed and may las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…The secondary outcomes of ventricular tachycardia occurrence and use of opiates were not different between the two groups, despite a higher prevalence of severe hypoxaemia in the group receiving air. These findings are consistent with previous studies that reported no relationship between hypoxia and ischaemia in coronary artery disease,36 37 but contrasted with another study that demonstrated a temporal relationship between nocturnal hypoxaemia and both ST-segment depression and arrhythmia after a MI 38…”
Section: Discussionsupporting
confidence: 91%
“…The secondary outcomes of ventricular tachycardia occurrence and use of opiates were not different between the two groups, despite a higher prevalence of severe hypoxaemia in the group receiving air. These findings are consistent with previous studies that reported no relationship between hypoxia and ischaemia in coronary artery disease,36 37 but contrasted with another study that demonstrated a temporal relationship between nocturnal hypoxaemia and both ST-segment depression and arrhythmia after a MI 38…”
Section: Discussionsupporting
confidence: 91%
“…A myocardial infarction or decompensated heart failure may be accompanied by local and generalized hypoxia and spontaneous nocturnal hypoxia with desaturation for hours is a frequent phenomenon in patients with severe coronary artery disease (11). Patients with coronary artery disease also respond differently to high altitudes than healthy persons.…”
Section: Cardiovascular Disease and Oxygenmentioning
confidence: 99%
“…Spontaneous nocturnal hypoxia with desaturation for hours is a frequent phenomenon in patients with severe coronary artery disease [2]. Left atrial, left ventricular (LV), and right ventricular (RV) end-systolic diameter fall during simulated extreme altitude [3] and during moderate altitude exposure [4].…”
Section: Introductionmentioning
confidence: 99%